Beispiel Nr: 02
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 9 x +5 + 4 z=13\\ 6 x +3 y + -5 z=17\\ 3 x -10 y + 6 z=23\\ \\ \\ \textbf{Rechnung:} \\ 9 x + 5 y + 4 z=13\\ 6 x +3 y -5 z=17\\ 3 x -10 y +6 z=23\\ D_h=\left|\begin{array}{ccc} 9\ & 5 & 4\\ 6&3 & -5\\ 3& -10 & 6 \\ \end{array}\right| \begin{array}{cc} 9\ & 5 \\ 6&3 \\ 3& -10 \end{array} \\ D_h=9 \cdot 3 \cdot 6+5 \cdot \left(-5\right) \cdot 3 +4 \cdot 6 \cdot \left(-10\right) - 4 \cdot 3 \cdot 3 -9 \cdot \left(-5\right) \cdot \left(-10\right) -5 \cdot 6 \cdot 6=-819 \\ D_x=\left|\begin{array}{ccc} 13\ & 5 & 4\\ 17&3 & -5\\ 23& -10 & 6 \\ \end{array}\right| \begin{array}{cc} 13\ & 5 \\ 17&3 \\ 23& -10 \end{array} \\ D_x=13 \cdot 3 \cdot 6+ 5 \cdot \left(-5\right) \cdot 23 +4 \cdot 17 \cdot \left(-10\right) - 4 \cdot 3 \cdot 23 - 13 \cdot \left(-5\right) \cdot \left(-10\right) -5 \cdot 17 \cdot 6=-2,46\cdot 10^{3}\\ D_y=\left|\begin{array}{ccc} 9\ & 13 & 4\\ 6&17 & -5\\ 3& 23 & 6 \\ \end{array}\right| \begin{array}{cc} 9\ & 13 \\ 6&17 \\ 3& 23 \end{array} \\ D_y=9 \cdot 17 \cdot 6+13 \cdot \left(-5\right) \cdot 3 +4 \cdot 6 \cdot 23 - 4 \cdot 17 \cdot 3 -9 \cdot \left(-5\right) \cdot 23 -13 \cdot 6 \cdot 6=1,64\cdot 10^{3} \\ D_z=\left|\begin{array}{ccc} 9\ & 5 & 13\\ 6&3 & 17\\ 3& -10 & 23 \\ \end{array}\right| \begin{array}{cc} 9\ & 5 \\ 6&3 \\ 3& -10 \end{array} \\ D_z=9 \cdot 3 \cdot 23+5 \cdot 17 \cdot 3 +13 \cdot 6 \cdot \left(-10\right) - 13 \cdot 3 \cdot 3 -9 \cdot 17 \cdot \left(-10\right) -5 \cdot 6 \cdot 23=819\\ x=\frac{-2,46\cdot 10^{3}}{-819} \\ x=3 \\ y=\frac{1,64\cdot 10^{3}}{-819} \\ y=-2 \\ z=\frac{819}{-819} \\ z=-1\\ L=\{3/-2/-1\} $